The Public Procurement System in Pakistan: A Critical Analysis - Zaidi, Syed Ali Mujtaba; Ashraf, Swera; Shah, Syed Asad Ali (Journal of Social Sciences and Management Studies, 2023)
This research paper aims to provide a comprehensive understanding of the public procurement system in Pakistan and explore contemporary electronic/online procurement methods to enhance transparency. The study employs a two-fold approach: initially showcasing the existing procurement landscape in Pakistan and subsequently proposing modern approaches for implementing a transparent electronic procurement system. A thorough literature review is conducted, incorporating publications, journal articles, government documents, regulations, laws, news articles, webpages, and a dissertation related to public procurement. The analysis extends to incorporate lessons learned from the procurement experiences of other countries, offering valuable insights for potential improvements in Pakistan's public procurement system. Using a conceptual analysis technique, the current tendencies and progress in procurement practices within Pakistan's public sector are extensively elucidated. The findings of this study contribute significantly to the understanding of the public procurement system in Pakistan, highlighting both its strengths and areas requiring improvement. Moreover, the proposed electronic procurement system, informed by international experiences, serves as a practical solution to ensure transparency, efficiency, and compliance within the public sector. This research paves the way for future studies and policy recommendations that can enhance procurement practices and ultimately foster sustainable development in Pakistan.